A rare case of primary umbilical endometriosis in a nulliparous female confirmed on imaging and histopathology: Case report - Jaswinder Kaur Mohi; Jasvir Singh; Amarjit Kaur; Samrin Haq; Navkiran Kaur (International Journal of Medical Research and Review, 2016)
Endometriosis is a common gynaecological condition, the pelvis being the most common site. Extrapelvic sites including intestinal tract, urinary tract, omentum, thorax, surgical scars and umbilicus are less common sites and are difficult to diagnose. Majority of extrapelvic cases occur at surgical scar sites. Occurrence of umbilical endometriosis in a patient without any previous surgical history is a very rare condition. So, we are going to report the case of a primary umbilical endometriosis in a 40 years old nulliparous female presented with complaints of pain abdomen associated with bleeding per vaginum and cyclical bleeding from umbilical region since 2 months.This paper summarises the topic of umbilical endometriosis and discusses the radiological and clinical implication of this unusual condition.